Short tandem repeat marker based evaluation of mutation drift equilibrium in Krishna Valley cattle - S. Rajesh Kumar; M.D. Kothekar; S.M.K. Karthickeyan; R. Saravanan; P. Kathiravan; P. Thangaraju (Journal of Livestock Biodiversity, 2025)
The present study was undertaken to evaluate the Krishna Valley cattle for the occurrence of genetic bottleneck based on microsatellite genotype data at 18 loci. Three different tests viz. sign test, standardized differences test and Wilcoxon sign rank test were utilized to evaluate the Krishna Valley cattle population for detecting the transient heterozygosity excess under different models of microsatellite evolution. Under infinite alleles model (IAM), all the three tests revealed significant heterozygosity excess while the stepwise  mutation  model  did  not  reveal  any  such  significant  heterozygosity  excess.  Under  the  two  phase  model  sign  test  and standardized differences test with the exception of Wilcoxon sign rank test revealed significant heterozygosity excess indicating the possible deviation of Krishna Valley cattle population from mutation drift equilibrium. However, the allele frequency distribution at different microsatellite loci revealed normal L-shape without any mode shift. The absence of mode shift indicates that the rare alleles have not been lost much, despite the severe reduction in the population size of Krishna Valley cattle.